The benefits and risks of caffeine to health: are you aware of it? / Nora Mohd Basir ... [et al.]. - Mohd Basir, Nora; Mohd Yusop, Noorezatty; Zulkifli, Muhammad Luqman; Rahim, Muhammad Shauqi; Nazli Suhardi, Najmuddin Haqimi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“Understanding caffeine's benefits and risks is essential for students who rely on it to stay awake and alert.” Caffeine, a stimulant drug, is widely used to enhance mental and physical performance and is commonly known as an energy booster [1]. It is found in various beverages, including coffee, tea, chocolate, and energy drinks. These drinks are popular across different age groups and can significantly boost alertness, improve mood, and reduce fatigue by increasing dopamine levels, a neurotransmitter associated with pleasure and reward. However, while caffeine offers several benefits, it can also have negative effects if consumed excessively. Too much caffeine can lead to headaches, high blood pressure, sleep disturbances, anxiety, stomach problems, shaky hands, and an increased heart rate [1] [2]. Despite these potential risks, many people are unaware that caffeine is present in beverages other than coffee, such as tea, energy drinks, and sodas, even though these drinks usually contain lower amounts of caffeine.